Fear of detachment from mobile phone: Nomophobia and suicidality among Malaysian university students before and during the COVID-19 pandemic - Pang, Khong Yun (Routledge, 2024)
The attachment to mobile devices during the COVID-19 pandemic has led to the possibility of increased nomophobia, which is the intense fear of losing access to one's mobile device. Therefore, this study aimed to determine if nomophobia was independently associated with suicidality before and during the COVID-19 pandemic among university students in Malaysia. This cross-sectional study had two-time points in data collection: one year before and one year into the COVID-19 pandemic. N = 806 university students aged >= 18 years completed an online questionnaire comprising the Nomophobia Questionnaire, Multidimensional Scale of Perceived Social Support, and the Suicidal Behaviors Questionnaire-Revised. A multiple logistic regression (controlling for gender, age, and social support) was conducted to determine the association between nomophobia and suicidality before and during the COVID-19 pandemic. The prevalence of severe nomophobia before and during the COVID-19 pandemic was 15.7% and 35.6% respectively. The level of nomophobia was significantly higher during the COVID-19 pandemic compared to pre-pandemic. Pre-pandemic, there were no significant associations. During the pandemic, participants with moderate (aOR 3.09, 95% CI 1.14-8.40], p = .027) and severe (aOR 3.57, 95% CI 1.25-10.20], p = .018) nomophobia had higher odds of suicide plan. During the pandemic, moderate and severe nomophobia were independently associated with more than three times higher odds for a lifetime suicide plan. Our study findings carry implications for the well-being of university students.